Bandwidth Enhancement Technique with Low Group Delay Variation CMOS Power Amplifier for UWB System - Sapawi, Rohana; Sahari, Siti Kudnie; Awang Salleh, Dayang Nur Salmi Dharmiza; Awang Mat, Dayang Azra; Zainol Murad, Sohiful Anuar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper introduced a bandwidth enhancement technique for ultra-wideband (UWB) transmitter design with low group delay variation for CMOS power amplifier (PA). Three stages of cascade common source topology are implemented to provide high gain with good gain flatness. Shunt peaking inductor is introduced at every stage of the introduced PA to improve the bandwidth and to achieve low group delay variation simultaneously. A resistive shunt feedback method is implemented at the first stage to acquire good input matching. The first and second stages attain gain at lower corner and upper-end frequency respectively, whilst the third stage smoothed the gain flatness curve. In addition, the theoretical analysis of group delay is investigated to determine the important design factor for low group delay variation in 3.1 to 10.6 GHz CMOS PA for UWB transmitters. The outcome of the research shows that a gain about 11.48 ± 0.6 dB at average, S11 less than -10 dB, and S22 less than -14 dB is achieved. Moreover, excellent group delay variation is acquired throughout the entire band, measuring about ±85.8 ps.